Asphaltene aggregation via dissipative particle dynamics - Oliveira, Fellipe Carvalho de (2021)
Asphaltenes compose the heaviest fraction of crude oil that can form nanoaggregates. These fractions can precipitate, clog pipes during extraction and processing, which can make the production process unfeasible. The kinetic conditions of asphaltene precipitation depend on the structure and size of the nanoaggregates formed. In this work, the molecular simulation was used to study the characteristics of asphaltene aggregation both in solution and on water-oil interfaces. The asphaltene aggregation process takes place over a large time scale, when compared to other atomistic phenomena. Diluted solutions of asphaltenes in toluene were analyzed, and the results of the radial distribution function and diffusion coefficient represented the experimental data well. In water-asphaltene-oil systems, cyclohexane was chosen as the oil phase. The decay curve of the interfacial tension as a function of the asphaltene concentration and the estimated critical micelle concentration is consistent with experimental data from the literature. The linear density profile of the asphaltene molecules at the interface was measured, as well as the distribution of contact angles between asphaltene molecules and the water/oil interface. In conclusion, the DPD method can be appropriately used to simulate both the structural and dynamic characteristics of asphaltenes in solution, moreover, it also describes well the asphaltene properties at the water/oil interface.